GOVERNANCE OF VILLAGE ADMINISTRATION IN THE DEVELOPMENT OF THE TOURISM SECTOR IN BITING VILLAGE, BADEGAN DISTRICT, PONOROGO REGENCY - Khoirunnisa Khoirunnisa; Yusuf Adam Hilman; Bambang Triono; Irvan Nur Ridho (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
This research aims to understand and describe village government management in the development of the tourism sector in Biting Village, Badegan District, Ponorogo Regency. The concept of Good Village Governance is used as the theoretical foundation, emphasizing transparency, accountability, and community participation as the main principles. This study employs a qualitative approach with data collection techniques through semi-structured interviews and documentation. Data analysis is conducted using the data analysis model from Miles, Huberman, and Saldana (2014), including data condensation, data display, and conclusion drawing. The results show that transparency is realized through the dissemination of information on policies, programs, and activities through various communication platforms. Accountability is evident in the monthly reporting of tourism funds and periodic evaluations. Community participation is enhanced through Village Deliberation forums and training involving various community components. The conclusion emphasizes the importance of transparency, accountability, and community participation in managing the tourism sector to achieve good and sustainable governance.